2019
DOI: 10.3390/app9040751
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Chalcedonite as a Biosorption Bed in the Treatment of Groundwater

Abstract: The conducted laboratory tests allowed determination of the efficiency of removing ammonium nitrogen, iron, and manganese in the biofiltration process on chalcedonite beds. The process of water purification was carried out by a single- and two-stage biofiltration method with gravitational and anti-gravitational flow. The study examined the extent to which chemical activation of the bed with potassium manganese (VII) affects the course of the nitrification process and the rate of biofilm formation. The obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…• fine mesopore volume (~2-5 nm) • SSA The impact of structural parameters of the filtration materials on the auto-activation process was the subject of previous studies [5,19]. The results of this study show that both the auto-activation time and the magnitude of the removal zone decrease with increasing pore volume and SSA (Figure 5).…”
Section: Auto-activation Researchmentioning
confidence: 57%
See 1 more Smart Citation
“…• fine mesopore volume (~2-5 nm) • SSA The impact of structural parameters of the filtration materials on the auto-activation process was the subject of previous studies [5,19]. The results of this study show that both the auto-activation time and the magnitude of the removal zone decrease with increasing pore volume and SSA (Figure 5).…”
Section: Auto-activation Researchmentioning
confidence: 57%
“…Mined chalcedonite is a sedimentary rock formed from dissolution, precipitation, and crystallization, derived from dead organisms living in warm and shallow seas. Similar to silica sand, chalcedonite is chemically homogenous and consists mostly of SiO 2 but is characterized by internal porosity in contrast to silica sand [5,19]. Chalcedonite is a mineral which occurs in the form of solid rock formations interleaved with chalcedonite silt; hence, the technology for the preparation of chalcedonite filter sand includes, among others, mechanical crushing and grinding of this mineral, rinsing and hydraulic classification, drying and dry fractionation [6,19].…”
Section: Characterization Of Filtration Materialsmentioning
confidence: 99%
“…For the first phase of the process, 3.43 mgO 2 /mgN is needed, while for the second phase, where the nitrite ion is oxidized to nitrate, the amount is 1.14 mgO 2 /mgN. It has been repeatedly confirmed that oxygen consumption is lower and is not stoichiometric to the amount of nitrogen removed [35]. The reason for this phenomenon may be, among others, a biosynthetic process during which oxygen is released.…”
Section: Resultsmentioning
confidence: 99%
“…Quartz sand or gravel are the most popular materials used in field operations based on natural coating [29,165,166,176,178,[182][183][184]. Among the less frequently used mineral filter media clinoptilolite [185], anthracite [167,183], or chalcedonite [128,186,187] can be mentioned. However, during the filtration of aerated water, the grains of filter media are gradually covered with iron and manganese oxyhydroxides.…”
Section: Coating Formationmentioning
confidence: 99%